ISO quality management system: A lesson from KLIA - Mohammed, Abdul Hakim; Baba, Maizan; L., Jawahar Nesan; Zakaria, Norhanim (2003)
This paper reports the ISO 9000 implementation at the construction of Kuala Lumpur International Airport (KLIA), a prestigious multibillion dollars project commissioned by the government of Malaysia, and presents a set of guidelines to effectively implement ISO quality systems in large construction projects. The study being undertaken for the past three years has been sponsored by the IRPA (Intensification of Research in Priority Areas), a premier national funding agency. The complete history of the ISO implementation in KLIA right from the inception of the project until its completion was studied through several means including a series of interviews with staff, and archival studies of quality records and voluminous implementation documents. This paper, while initially highlighting the pitfalls observed in the implementation stage and other major problems as identified from the quality records, finally proposes a set of guidelines. The guidelines are conceptual and broadly address the major issues that are critical to the implementation of the ISO Quality Management System (QMS) in large construction projects. They should be seen as an aiding mechanism to improve the quality performance of the construction participants. It must also be noted that the guidelines have been developed from the perspective of the Client (Owner)